Research methods : a concise introduction to research in management and business consultancy - Crowther, David; Lancaster, Geoffrey, 1938-; Lancaster, Geoffrey, 1938- (Amsterdam ; Boston ; London : Butterworth-Heinemann, 2009)
Offering guidance on a wide variety of research management topics, this text provides an overview of the entire field, identifying the key issues that students need to be aware of when carrying out research
Includes bibliographical references (p. [219]-226) and index
Keywords: Management -- Research